The Effect Of Body Image Psycoeducation On Students - Novita Maulidya Jalal; Perdana Kusuma; Hadjar Nurul Istiqamah; Wilda Ansar (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
Student body image is formed from attitudes and perceptions of characteristics in terms of physical or appearance. This study aims to determine whether there is an influence of psychoeducation on body image in students. This study used a quasi-experimental method with a pretest-posttest control group design. The instrument used is a body image questionnaire that has been developed with 9 statement items. The research subjects were students at one of the universities in Makassar, totaling 44 students consisting of 22 experimental groups and 22 control groups. The data analysis used in this study was the t-independent sample test. The results showed that there was no significant difference in body image scores when viewed from the two groups. However, based on independent sample t-test, it shows that the mean for the control group is 27.5 and the experimental group is 28.0, which means that the average value of the experimental group is higher than that of the control group.